A highly efficient zinc catalyst for selective electroreduction of carbon dioxide in aqueous NaCl solution1. Issue 32 (28th August 2015) - Quan, Fengjiao; Zhong, Dan; Song, Hancheng; Jia, Falong; Zhang, Lizhi
<x xml:space="preserve">Abstract</x> A low-cost nanoscale zinc catalyst, prepared by a facile electrochemical strategy, exhibits high activity toward electrochemical reduction of CO2 to CO with up to 93% Faraday efficiency in aqueous NaCl solution.